2018
DOI: 10.1039/c8ta06726k
|View full text |Cite
|
Sign up to set email alerts
|

A facile method for scalable synthesis of ultrathin g-C3N4 nanosheets for efficient hydrogen production

Abstract: Scalable production of ultrathin g-C3N4 nanosheets for efficient water splitting by the aid of kitchen-available melamine foam (MF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…To further apply the stabilized PdNPs in the porous liquid, they are transferred onto carbon nitride nanosheets and serve as photocatalysts for the production of hydrogen from water. PdNPs@C 4 R was chosen as a representative due to its superior dispersion and stabilization activities and was loaded as a co-catalyst on carbon nitride prepared according to the procedures reported by us before . First, we optimized the loading amount of PdNPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further apply the stabilized PdNPs in the porous liquid, they are transferred onto carbon nitride nanosheets and serve as photocatalysts for the production of hydrogen from water. PdNPs@C 4 R was chosen as a representative due to its superior dispersion and stabilization activities and was loaded as a co-catalyst on carbon nitride prepared according to the procedures reported by us before . First, we optimized the loading amount of PdNPs.…”
Section: Resultsmentioning
confidence: 99%
“…35−38 PdNPs@C 4 R was chosen as a representative due to its superior dispersion and stabilization activities and was loaded as a co-catalyst on carbon nitride prepared according to the procedures reported by us before. 39 First, we optimized the loading amount of PdNPs. Briefly, 5 mg of carbon nitride powder was dispersed in 10 mL of an aqueous solution with triethanolamine (10 vol %) as a sacrificial agent, and then x μL (x = 6, 9, 15, 20, 30) of PdNPs@C 4 R methanol solution (4.27 mg mL −1 ) was added, respectively (Figure 3a).…”
Section: As Shown Inmentioning
confidence: 99%
“…For pristine CNS, the broad peaks between ∼3000 and ∼3400 cm –1 correspond to the N–H stretching vibration and the O–H band. The peaks in the ∼1200–1700 cm –1 region are assigned to sp 2 CN stretching vibration modes and the aromatic sp 3 C–N bonds. , Moreover, the intense peak at ∼807 cm –1 can be due to the out-of-plane skeletal bending modes of triazine. It is found that there are no obvious changes between the pristine CNS and a series of 3D CCNS- H , indicating that the HMTA treatment did not change the skeleton structure of g-C 3 N 4 .…”
Section: Resultsmentioning
confidence: 99%
“…In the control experiment (Figure d), no H 2 was detected for the PhBp-CTF without the Pt cocatalyst, while a PHE rate of 242 μmol g –1 h –1 was recorded for PhBp-CTF-Ir without the Pt cocatalyst. This result shows that the Ir complexes act as not only an efficient photosensitizer but also an effective proton reduction catalyst. The apparent quantum efficiency (AQE) for PHE was calculated to compare the photocatalytic efficiency of the two CTFs. According to the H 2 amount generated in an average of 1 h, the AQE was measured to be 1.37% (420 nm) for PhBp-CTF and 2.36% (420 nm) for PhBp-CTF-Ir.…”
Section: Resultsmentioning
confidence: 99%